Comparative Study of Dezocine and Ketorolac Tromethamine in Patient-Controlled Intravenous Analgesia of Laparoscopic Cholecystectomy - Yidan Ying; Shuke Fei; Zhiying Zeng; Xiaoyong Qu; Zemin Cao (Frontiers in Surgery, 2022)
PurposeThis study aimed to observe the application value of dezocine and ketorolac tromethamine in patient-controlled intravenous analgesia (PCIA) of patients undergoing laparoscopic cholecystectomy (LC).MethodsA total of 154 patients who underwent LC surgery in our hospital and received PCIA after surgery from September 2020 to September 2021 were selected, they were divided into group A (n = 77) and group B (n = 77). Group A was given dezocine and group B was given ketorolac tromethamine. The analgesia, sedation, comfort, and adverse reactions of the two groups were closely observed at 4, 8, 12, and 24 h after surgery.ResultsAt 4, 8, 12, and 24 h after surgery, the visual analog scale scores in group B were lower than those in group A (P < 0.05). At 4, 8, 12, and 24 h after surgery, the Ramsay scores in group B were higher than those in group A (P < 0.05). At 4, 8, 12, and 24 h after surgery, there was no significant difference in Bruggrmann comfort scale scores between the two groups (P > 0.05). There was no significant difference in the incidence of adverse reactions between the two groups (P > 0.05).ConclusionBoth dezocine and ketorolac tromethamine have high clinical application value in patients who underwent LC surgery and received PCIA, with higher patient comfort and fewer adverse reactions. But compared with dezocine, ketorolac tromethamine can achieve better sedative and analgesic effects, which is worthy of clinical promotion.